Provenance and tectonic setting of the Paleo- to Mesoproterozoic Dongchuan Group in the southwestern Yangtze Block, South China: Implication for the breakup of the supercontinent Columbia - Wang, Wei; Zhou, Mei-Fu (Tectonophysics, 2014)
The Paleoproterozoic to Mesoproterozoic (1742–1503Ma) Dongchuan Group in the southwestern Yangtze Block is a rift-related sedimentary sequence that was associated with the breakup of the supercontinent Columbia and is particularly important for the possible linkage between the Yangtze Block and other continents in Columbia. The Dongchuan Group consists of the Yinmin, Luoxue, Etouchang and Luzhijiang formations from the base upward. Sandstones from the Yinmin Formation are mainly arkose containing dominant K-feldspar with subordinate plagioclase and quartz. Abundant feldspar and high Qm/Q ratios (0.94–1) are indicative of plutonic sources. These sandstones have high La/Sc (3.06 to 4.32), low Sc/Th (0.74 to 1.15) and Co/Th (0.85 to 1.52) and highly evolved Nd isotopes (εNd(t)=−6.2 to −8.2), consistent with an old, felsic igneous source. Detrital zircons of this formation have two major age groups at 2602–2887Ma and 2224–2392Ma. Siltstones of the Etouchang Formation have detrital zircons with a prominent age peak at ~2560Ma and several subordinate peaks at ~2180Ma, ~2100Ma and ~1900Ma. They have high Sc/Th (1.00–7.08), Co/Th (0.13 to 6.31) and εNd(t) (−2.1 to −6.7), significantly different from the Yinmin Formation. The Yinmin Formation is interpreted to deposit during the initial stage of extensional rifting receiving detritus of granites and TTG mainly from uplifted shoulder. The Etouchang Formation more likely formed in a passive margin with sedimentary material largely from cratonic sources. Paleoproterozoic to Mesoproterozoic rift basins in the southwestern Yangtze Block, north Australia and northwestern Laurentia have remarkably similar provenance and tectonic setting in their lower part (1742–1596Ma), but significantly different since the onset of the Etouchang Formation (ca. 1596Ma). Therefore, the southwestern Yangtze Block was likely connected with the north Australia and northwestern Laurentia in Columbia and drifted away from these continents on or before ca. 1596Ma. •The Dongchuan (DC) Group in SW Yangtze Block formed between 1742Ma and 1503Ma.•Remarkably different provenance for the lower and upper DC groups.•Sedimentation of the DC Group was associated with rifting setting to passive margin.•The SW Yangtze Block was connected with N Australia and NW Laurentia in Columbia.•The Yangtze Block drifted away from adjacent continents on or before ca. 1590Ma.